Sustainable, greenhouse gas derived fermented protein in canine diets—a pilot study - Babu, Ravindra; Padmanabhan, Sreedevi; Ganesan, Ravikumar; Subbian, Ezhil; Van, Thi Thu Hao; Eri, Rajaraman (Frontiers in Veterinary Science, 2025)
Sustainability concerns have increased consumer demand for non-animal-derived proteins and the search for novel, alternative protein sources. The nutritional sustainability of the food system without compromising the nutrient quality, composition, digestibility and consumption is pivotal. As with farmed livestock, it is imperative to ensure the well-being and food security of companion animals and to develop sustainable and affordable pet foods. The current pilot study was conducted to determine the effect of greenhouse gas-derived novel, fermented protein ingredient in beagle dogs. The greenhouse gas-derived fermented protein is an alternative protein ingredient with optimal nutritional factors and provides traceability, significantly optimizes the use of land and water, and provides sustainability to the feed value chain of canine diets. Three experimental groups including control, 5 and 10% inclusion of high protein ingredients were included in the study and the results suggest that the fermented protein is palatable and acceptable at 5 and 10% inclusions in the diets of dogs. The present study shows no significant difference in general alertness, clinical symptoms, water consumption and social behavior of dogs between 5 and 10% fermented protein inclusion in canine diets. The diversity of the bacterial community did not change after supplementation with the tested protein source in dogs. Only a few bacterial genera differed significantly in relative abundance between the experimental groups. Feed consumption, faecal scoring and the microbiome data results of this pilot study on the use of novel, methane gas derived, bacterial SCP as a protein ingredient in the canine diets, would pave way for more and more inclusion of such novel alternative protein sources in the pet food industry.